Preservative-treated wood having laser-processed micro-holes and manufacturing method thereof
Patent Information
- Application Number
- KR1020250168264
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-11-10
- Publication Date
- 2026-09-02
- Estimated Expiration
- 2045-11-10
Smart Images

Figure 112025125164011-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention is the result of the Regional Innovation Center University Support System (RISE) conducted with funding from the Ministry of Education and Gyeongsangbuk-do in 2025 and with support from the Gyeongbuk RISE Center. (2025-RISE-15-205) The present invention relates to a technology for manufacturing preservative-treated wood, and more specifically, to a preservative-treated wood equipped with laser-processed micro-holes that form micro-holes on the surface of wood using a laser, inject a preservative agent through these holes, and then prevent the leaching of the agent with a multi-layer sealing process, and a method for manufacturing the same. Background Technology
[0002] Wood is widely used in the construction and landscaping fields due to its excellent thermal insulation and eco-friendliness; however, it poses a problem of easily deteriorating due to biological and physicochemical degradation factors. To address this issue, preservation technologies involving the injection of preservatives into wood have been developed.
[0003] Conventional preservative-treated lumber manufacturing technologies are broadly classified into mechanical incising and laser hole drilling methods. Mechanical incising involves using a blade to create millimeter-sized cut marks on the wood surface; however, this method suffers from severe surface damage that degrades aesthetics and causes problems such as the formation of a dense layer at the blade indentation site, which actually hinders the penetration of the preservative. In particular, it presented significant limitations as it was very difficult to apply to hard-to-penetrate species such as larch and Douglas fir.
[0004] To address these issues, a laser-based micro-hole drilling technology has been proposed. Korean Registered Patent No. 10-2661450 discloses a technology that uses a laser to form micro-holes ranging in size from tens to hundreds of micrometers and injects a preservative through them. This technology has the advantage of enabling the injection of preservatives into difficult-to-implant wood species while minimizing damage to the wood surface.
[0005] However, conventional laser hole drilling methods had a fundamental problem in that the formed micro-holes acted as both injection and release pathways for the preservative. Specifically, due to the open, direct hole structure, the injected preservative would backflow and release to the outside in rainy or high-humidity environments. Furthermore, there was a limitation in that the preservative concentrated only around the holes, leaving the areas between the holes untreated, resulting in uneven preservative performance.
[0006] Furthermore, the carbonized layer generated during laser processing hinders the penetration of chemicals, and the persistence of internal moisture and sap causes pressure loss and behavioral instability during pressurized injection. Due to these issues with conventional technology, there has been an urgent need to develop a preservative-treated wood manufacturing technology that simultaneously ensures long-term durability and environmental safety. Prior art literature
[0007] 1. Republic of Korea Patent No. 10-2661450 "System for manufacturing preservative-treated wood using a laser" 2. Republic of Korea Patent No. 10-2690562 "Method for manufacturing preservative-treated wood using a laser and preservative-treated wood manufactured thereby" 3. U.S. Patent US 8,167,304 B2 "Micronized wood preservative formulations comprising boron compounds" The problem to be solved
[0008] The present invention has been devised to solve the problems of the prior art as described above. The objective of the present invention is to provide a preservative-treated wood and a method for manufacturing the same, which implements an asymmetric structure in which micro-holes formed by a laser act as an injection path for a preservative agent but not as an elution path.
[0009] Another objective of the present invention is to provide a preservative wood and a method for manufacturing the same, which realizes the immobilization of a preservative by forming the shape of the micro-holes into a tapered shape with a narrow entrance and a wide bottom, and by surface-functionalizing the hole walls to induce chemical bonding with the preservative.
[0010] Another objective of the present invention is to provide a preservative-treated wood and a method for manufacturing the same, which effectively blocks the leaching of preservatives even under changes in the external environment by implementing a multi-seal system comprising hydrogel microparticles that selectively seal microholes in response to moisture, wax impregnation, and UV-curable polyurethane coating.
[0011] Another objective of the present invention is to provide a method for manufacturing preservative-treated wood that effectively removes moisture and sap from within the wood and relaxes the cell wall structure through a pretreatment process using ultrasound and microwaves, thereby improving the penetration and uniformity of the preservative agent.
[0012] Another objective of the present invention is to provide a method for manufacturing preservative-treated wood that simultaneously achieves productivity and surface functionalization using a dual-wavelength laser, and simultaneously implements preservative performance and agent immobilization using a hybrid agent of borate and silane. means of solving the problem
[0013] To achieve the above objectives, the preservative wood having laser-processed micro-holes according to the present invention comprises a plurality of micro-holes that extend from the surface of the wood body into the interior by laser processing and have an opening portion narrower than the bottom portion, a preservative holding layer injected through the micro-holes and retained inside the wood body, hydrogel micro-particles disposed at the opening portion of the micro-holes, and a surface sealing layer covering the surface of the wood body.
[0014] Meanwhile, the microholes may include a surface functionalization layer formed on the wall of the hole, and it is preferable that the preservative-holding layer includes a silane network structure that chemically bonds with the borate component and the surface functionalization layer. In this case, the hydrogel microparticles may include hydrogel microparticles that swell in response to moisture, and the surface sealing layer may include a wax impregnated layer and a UV-curable polyurethane coating layer on top thereof. Additionally, the microholes have a tapered shape, and the silane network structure may include Si-O-Si bonds and Si-OC bonds. Furthermore, the hydrogel microparticles may perform a microvalve function that selectively closes the entrance of the microholes upon the inflow of external moisture, the surface functionalization layer may include polar groups formed by UV laser treatment, and it is preferable that the hydrogel microparticles include an acrylate-based superabsorbent polymer.
[0015] Meanwhile, to achieve the above objectives, a method for manufacturing preservative wood having laser-processed micro-holes according to the present invention comprises the steps of: forming a plurality of micro-injection holes extending from the surface of the wood inward and having an opening portion narrower than the bottom portion; injecting a preservative agent through the micro-injection holes; forming hydrogel micro-particles at the opening portion of the micro-injection holes; and forming a surface sealing layer on the surface of the wood.
[0016] At this time, the step of forming micro-injection holes may include processing the micro-injection holes with a laser of a first wavelength and surface functionalizing the walls of the micro-injection holes with a laser of a second wavelength, and the step of injecting a preservative may include injecting a hybrid agent containing borate and silane in a vacuum-pressurization cycle. Additionally, the step of pre-treating the wood with ultrasound and microwaves before forming the micro-injection holes may be further included, the step of forming hydrogel microparticles may include selectively placing moisture-reactive hydrogel microparticles at the entrance, and the step of forming a surface sealing layer may include impregnating with wax and coating with UV-curable polyurethane.
[0017] Additionally, the method may further include a step of repeating a vacuum-pressurization cycle between the ultrasonic and microwave pretreatment step and the preservative injection step, the laser of the first wavelength may be a CO₂ laser and the laser of the second wavelength may be a UV laser, and the hybrid agent may be in an aqueous solution state adjusted to a pH of 4.5 to 5.5. Finally, the micro-injection hole may be formed in a tapered shape by adjusting the focus of the laser. Effects of the invention
[0018] According to the present invention, the laser-formed tapered microholes, the surface functionalization layer, the moisture-reactive hydrogel sealing layer, the wax impregnation layer, and the UV-curable polyurethane coating layer form physical, chemical, dynamic, and mechanical barriers, thereby effectively blocking the leaching of preservatives.
[0019] In addition, ultrasonic and microwave pretreatments open the peat membrane of the wood cell walls and effectively remove internal moisture and sap, thereby improving the penetration depth of the preservative.
[0020] Furthermore, the performance of the product can be significantly improved by rapidly forming a tapered hole with a CO₂ laser, removing the carbonized layer with a UV laser, and introducing polar groups to enhance bonding with silane. Brief explanation of the drawing
[0021] FIG. 1 is a cross-section of a preservative-treated wood having laser-processed micro-holes according to the present invention. Figure 2 is a diagram illustrating the operating state of hydrogel microparticles according to humidity. FIG. 3 is a flowchart showing the overall process of a method for manufacturing preservative-treated wood having laser-processed micro-holes according to the present invention. FIG. 4 is a detailed flowchart illustrating the preprocessing steps of the present invention illustrated in FIG. 3. Specific details for implementing the invention
[0022] Hereinafter, the present invention will be described in detail with reference to preferred embodiments of the invention and the accompanying drawings, under the premise that identical reference numerals in the drawings refer to identical components.
[0023] When it is stated in the detailed description of the invention or the claims that one component "includes" another component, this shall not be interpreted as being limited to being composed solely of said component unless specifically stated otherwise, but shall be understood as potentially including other components.
[0024] Hereinafter, embodiments of the present invention will be described in detail with reference to the attached drawings.
[0025] FIG. 1 is a cross-section of a preservative-treated wood having laser-processed micro-holes according to the present invention.
[0026] The preservative wood (100) as shown in FIG. 1 has an asymmetric structure in which the laser-formed micro-holes (110) effectively serve as an injection path for the preservative agent but not as an leaching path.
[0027] This asymmetric structure is realized by the tapered shape of the microholes (110), chemical immobilization of the preservative holding layer (120), selective blocking of the hydrogel microparticles (130), and the surface sealing layer (140).
[0028] To this end, the preservative wood (100) of the present invention comprises a plurality of micro-holes (110) formed in the wood body, a preservative holding layer (120) injected through the micro-holes and retained inside the wood, hydrogel micro-particles (130) selectively placed at the entrance of the micro-holes, and a surface sealing layer (140) covering the entire surface of the wood.
[0029] The micro-hole (110) is formed by laser processing extending inward from the surface of the wood, and has a tapered shape in which the entrance (111) is narrower than the lower part (112).
[0030] The diameter (D1) of the inlet portion (111) has a range of 50 to 150 micrometers, preferably 80 to 130 micrometers.
[0031] These fine inlet diameters are barely perceptible to the naked eye, so they function sufficiently as an injection route for preservatives without damaging the aesthetics of the wood.
[0032] The diameter (D2) of the lower part (112) has a range of 200 to 500 micrometers, preferably 250 to 400 micrometers.
[0033] The lower structure (112), which is enlarged compared to the inlet (111), acts as a physical barrier that suppresses the backflow of the drug due to capillary action.
[0034] The depth (L) of the microhole (110) ranges from 0.5 to 15 millimeters, preferably from 3 to 8 millimeters.
[0035] A surface functionalization layer (113) is formed on the hole wall of the microhole (110). The surface functionalization layer (113) refers to a state in which the carbonized layer is removed by UV laser treatment and polar groups, particularly hydroxyl groups (-OH), are introduced. These polar groups promote chemical bonding with the silane compound described later, thereby contributing to the immobilization of the preservative agent.
[0036] It is preferable to use a nanosecond or picosecond pulsed UV laser with a wavelength of 355 nanometers and to perform two or more passes with an energy density of 0.2 to 0.5 J / cm².
[0037] The preservative holding layer (120) refers to a layer in which the preservative injected through the micro-holes (110) is distributed inside the wood.
[0038] The preservative may use a borate component and a silane compound. The borate is used as borax, boric acid, or a mixture thereof at a concentration of 2 to 4 weight%, preferably 3 weight%. The silane compound is selected from one or more of γ-methoxypropyltrimethoxysilane (GMPTS), γ-glycidoxypropyltrimethoxysilane (GPTMS), and γ-mercaptopropyltrimethoxysilane (MPTMS) and used at a concentration of 3 to 5 weight%, preferably 4 weight%.
[0039] Silane compounds are hydrolyzed under weakly acidic conditions of pH 4.5 to 5.5 to form silanol groups (-Si-OH), and these form a three-dimensional network structure of Si-O-Si bonds through a condensation reaction.
[0040] At the same time, the silanol groups react with the polar groups of the surface functionalization layer (113) and the hydroxyl groups of the wood cell wall to form Si-OC bonds. This silane network structure can physically capture and chemically fix the borate components, thereby suppressing their leaching to the outside to a significant degree.
[0041] The hydrogel microparticles (130) consist of moisture-reactive hydrogel microparticles selectively placed at the entrance (111) of the microhole (110). The hydrogel uses an acrylate-based superabsorbent polymer, in particular sodium polyacrylate or poly(acrylamide-co-acrylic acid) copolymer, and the average particle size is 10 to 50 micrometers, preferably 20 to 40 micrometers. This size is smaller than the diameter of the entrance (111) of the microhole, so that the hole is not blocked in a dry state, while effectively sealing the hole when swollen.
[0042] Hydrogel microparticles are dispersed and coated onto the wood surface with an application amount of 0.5 to 1.0 g / m², preferably 0.8 g / m². The application is performed by finely spraying a hydrogel aqueous dispersion of 1 to 2 weight%, and is selectively concentrated around the entrance (111) of the microhole. Drying is performed at 40 to 60°C for 10 to 20 minutes to ensure that the hydrogel particles are stably fixed to the entrance.
[0043] The surface sealing layer (140) is composed of a double structure of a wax impregnated layer (141) and a UV-curable polyurethane coating layer (142).
[0044] The wax impregnation layer (141) is formed by using a mixture of paraffin wax and carnauba wax and immersing the wood in wax heated to 80 to 100°C, preferably 90°C, for 5 to 10 minutes. The wax penetrates into the micro-holes (110) and the micro-pores on the surface of the wood to form a hydrophobic barrier, thereby blocking the penetration of external moisture and inhibiting the leaching of preservatives.
[0045] To avoid hindering moisture contact of the hydrogel microparticles, the wax is immersed for a short time of 1 to 3 minutes in a low-viscosity dilution (5 to 10 wt% mineral oil mixture) to minimize residual amount. UV-curing polyurethane is used at a concentration of 10 to 20 g / m², limited to a single application to maintain a total film thickness of 20 to 40 μm, and a product with a water vapor permeability (MVTR) ≥ 800 g / m²·day (based on 23 ℃, 50% RH) is used.
[0046] A UV-curable polyurethane coating layer (142) is formed on top of a wax-impregnated layer (141) and serves as the outermost protective layer. The UV-curable polyurethane is composed mainly of an acrylate-modified urethane oligomer, and a liquid resin with a viscosity of 100 to 300 cPs is applied 2 to 3 times at a rate of 30 to 60 g / m². After each application, UV light with a wavelength of 385 to 405 nanometers is irradiated at a rate of 1 to 2 J / cm² to cure the coating, and the final coating layer thickness is 60 to 150 micrometers, preferably 120 micrometers.
[0047] FIG. 2 is a diagram illustrating the operating state of hydrogel microparticles according to humidity, where FIG. 2(a) shows the state when dry and FIG. 2(b) shows the state when wet.
[0048] Referring to FIG. 2(a), the hydrogel microparticles (130) exist in a shrunken state in the dry state. At this time, the size of the hydrogel particles is reduced to 10 to 20% of their original size and does not block the entrance (111) of the microhole (110). Therefore, air permeability between the inside and outside of the wood is maintained, allowing the wood to breathe and preventing excessive accumulation of internal moisture. This plays an important role in maintaining the long-term durability of the wood.
[0049] However, referring to FIG. 2(b), when external moisture enters during the rainy season or other high-humidity environments, the hydrogel microparticles (130) immediately swell and increase in volume to 200 to 800% of their original size, preferably 300 to 500%. The swollen hydrogel completely seals the entrance (111) of the microhole (110). This selective expansion prevents external moisture from penetrating into the wood through the microhole, while simultaneously preventing the internal preservative from dissolving in the moisture and leaching out to the outside.
[0050] Meanwhile, the swelling-shrinking process of this hydrogel is reversible, so when humidity decreases, the hydrogel shrinks again to restore breathability, and when humidity increases, it swells again to seal.
[0051] In the specification, "swelling" means an effective increase in volume under conditions where (i) surface condensation begins at a relative humidity of 95% or higher, or (ii) liquid water, such as rainwater or condensate, comes into contact with the inlet. Under these conditions, the hydrogel reaches functional swelling within a few seconds to tens of seconds upon contact with water, and within minutes in a high-humidity condensation environment.
[0052] This means that it is possible to respond quickly even in the event of sudden rainfall or a rise in humidity. Conversely, the drying process proceeds relatively slowly, returning to its original size over 2 to 4 hours, so it does not respond to temporary changes in humidity and has the selectivity to maintain the sealed state only in a continuous high-humidity environment.
[0053] The elements of the present invention described above interact organically with one another to create an unpredictable synergistic effect.
[0054] For example, tapered micro-holes alone are merely simple physical pathways and, conversely, cause problems such as increased resistance to drug injection due to the narrow opening. Furthermore, surface functionalization by UV laser alone introduces polar groups only to the wood surface and is unrelated to internal penetration.
[0055] However, when these two elements are combined, the UV laser undergoes multiple reflections in the space widened at the bottom due to the tapered shape, resulting in uniform surface functionalization across the entire wall surface of the hole. This corresponds to a phenomenon that is impossible in a simple straight hole.
[0056] The tapered shape improves the beam approach angle and scan accessibility, and increases diffuse and multiple scattering light from the inner wall, helping to facilitate uniform photochemical surface functionalization across the entire wall surface of the hole.
[0057] The polar groups formed in this way induce chemical bonding across the entire inner wall of the hole during subsequent silane treatment, enabling chemical immobilization in the microholes, which were previously a simple physical pathway.
[0058] Furthermore, although hybrid agents of borates and silanes exhibit excellent preservative performance, they have a fatal drawback: their high water solubility leads to easy leaching. When silane is used alone, it forms a network but has no preservative performance on its own. The surface functionalization layer alone merely improves wettability.
[0059] However, chemical anchoring becomes possible through the combination of these three elements. Specifically, hydroxyl groups introduced by UV treatment form covalent bonds (Si-OC) with silanol groups (-Si-OH) generated by the hydrolysis of silanes, and simultaneously, a three-dimensional Si-O-Si network is constructed through the condensation of silanes. It is believed that the Si-O-Si network and Si-OC bonds formed under the above conditions contribute to the physical capture and chemical immobilization of borate components. Accordingly, a reduction in leaching is expected.
[0060] In addition, the combination of the hydrogel suture layer and the tapered hole also produces an unexpected and significant effect.
[0061] When hydrogel is applied to a flat surface, it diffuses only in the transverse direction upon swelling, resulting in minimal suturing effect. Since the tapered hole alone remains an open pathway, it cannot prevent moisture penetration.
[0062] However, if the hydrogel is selectively placed at the entrance of the tapered hole, when swelling occurs, the hydrogel gets stuck in the narrow entrance (111) and is induced to expand only in the direction of the wide space (112) at the bottom. This is based on a principle similar to a rubber stopper getting stuck in a bottle neck, and a phenomenon occurs in which the sealing force becomes stronger as the internal pressure increases.
[0063] Hereinafter, with reference to the attached drawings, we will examine the method for manufacturing preservative-treated wood equipped with laser-processed micro-holes according to the present invention in a chronological order.
[0064] FIG. 3 is a flowchart showing the overall process of a method for manufacturing preservative-treated wood having laser-processed micro-holes according to the present invention, and FIG. 4 is a detailed flowchart showing the pretreatment step (S10) of FIG. 3 in detail.
[0065] First, prepare the wood to be treated with preservatives. Various tree species are suitable, such as larch, Douglas fir, pine, and spruce.
[0066] The initial moisture content of the wood should be 12 to 25%, and if it is excessively dry or wet, a separate moisture-regulating process may be performed. It is desirable to wash the wood with hot water at 25 to 35°C for 5 minutes to remove dust, resin, and other foreign substances from the surface.
[0067] Meanwhile, the pretreatment step (S10) consists of three detailed processes, as shown in FIG. 4: ultrasonic treatment (S11), microwave heating (S12), and vacuum-pressurization cycle (S13).
[0068] Through a pretreatment process, moisture and sap are removed from within the wood and the cell wall structure is relaxed, thereby maximizing the efficiency of subsequent laser processing and drug injection.
[0069] Ultrasonic treatment (S11) is performed at a frequency of 20 to 40 kHz, preferably 35 kHz, for 5 to 10 minutes, most preferably for 7 minutes.
[0070] Immerse the wood in an ultrasonic tank, maintaining a water depth of 50 to 100 mm and ensuring a spacing of at least 5 mm between samples so that cavitation occurs uniformly.
[0071] Ultrasonic cavitation destroys the pit membranes of wood cell walls and relaxes the cell walls to form micro-channels. The collapse energy of the micro-bubbles generated during this process produces locally very high pressure and high temperature heat, effectively opening up the internal structure of the wood.
[0072] Microwave heating (S12) is performed at a frequency of 2.45 GHz with an output of 500 to 1000 W, preferably 700 W. An intermittent irradiation method is adopted to prevent local overheating and carbonization inside the wood during continuous irradiation.
[0073] For example, a cycle of 60 seconds of irradiation followed by a 60-second rest and then 60 seconds of irradiation is applied, and the total irradiation time is adjusted within the range of 60 to 180 seconds depending on the thickness of the wood. Microwaves selectively heat the moisture inside the wood to lower viscosity and promote evaporation.
[0074] In particular, since the viscosity of the sap decreases exponentially with increasing temperature, the fluidity of the sap increases significantly when heated to 60 to 90°C. The surface temperature of the wood is monitored in real time using an infrared thermometer and controlled so as not to exceed 90°C.
[0075] The vacuum step is -0.08 MPa for 10 to 15 minutes, and the pressurization step is 0.8 to 2.0 MPa for 8 to 15 minutes, and this cycle is repeated 2 to 3 times. Depending on the wood type, thickness, and density, the optimal point between the introduction depth and mechanical stability is selected based on approximately 1.2 MPa.
[0076] In the vacuum stage, internal air and volatile substances are removed from the wood, and in the pressurization stage, residual moisture and sap are extruded as the cell walls are compressed. Repeated pressure changes induce a pumping effect within the wood, allowing the treatment effect to reach deep into the wood.
[0077] Once the pretreatment is complete, the preservative wood manufacturing process begins in earnest.
[0078] First, in the step (S20) of processing a tapered hole with a CO₂ laser, the pre-treated wood is fixed to the bed of the laser processing device.
[0079] The CO₂ laser is set to a wavelength of 10.6 μm and a spot size of 80 to 120 μm. It is preferable to use a pulse mode, and the heat-affected zone is minimized by setting the pulse frequency to 1 to 10 kHz and the duty cycle to 20 to 50%.
[0080] The laser focus is dynamically controlled to form a tapered hole. Initially, the focus is directed toward the wood surface to form the entrance, and the focus is gradually moved downward while simultaneously increasing the output to create a tapered shape that widens at the bottom. The target dimensions are an entrance diameter (D1) of 50–150 μm, a bottom diameter (D2) of 200–500 μm, and a depth (L) of 0.5–15 mm. The upper dimension limit is selected based on the wood species and resin content, and if necessary, carbonization and cutting debris evacuation can be improved through gas assistance (air / oxygen) or suction assistance.
[0081] The holes are arranged in a square grid or hexagonal pattern, and the pitch is set to 0.6 to 1.5 mm, preferably 1.0 mm. It is desirable to have an edge offset of 2 to 3 mm at the wooden corners to prevent corner damage.
[0082] Next, in the step (S30) of surface functionalizing the hole wall with a UV laser, UV laser treatment is performed at the same location immediately after CO₂ laser processing.
[0083] The UV laser uses an Nd:YAG third harmonic laser with a wavelength of 355 nm and operates in nanosecond (ns) or picosecond (ps) pulse mode. The energy density is set to 0.2 to 0.5 J / cm², and the scan speed is set to 50 to 200 mm / s.
[0084] UV laser treatment is performed in two or more passes; in the first pass, the carbonized layer generated during CO₂ laser processing is removed, and in the second pass, photochemical modification of the wood components is induced. UV photon energy (3.5 eV) selectively cleaves the CC and CO bonds of lignin and hemicellulose to generate polar functional groups such as carboxyl groups (-COOH) and hydroxyl groups (-OH) on the surface. Since the generation of polar groups increases by more than 30% when treated in an oxygen atmosphere, oxygen gas can be supplied at a flow rate of 1 to 5 L / min if necessary.
[0085] In the step of injecting the preservative (S40), the laser-processed wood is transferred to a preservative injection device. First, a hybrid preservative is prepared. A silane compound (selected from GMPTS, GPTMS, and MPTMS) is dissolved in an aqueous glacial acetic acid buffer solution with a pH of 4.5 to 5.5 at a concentration of 3 to 5 weight%, preferably 4 weight%. Pre-hydrolysis of the silane is induced by stirring at 25 to 30°C for 30 to 60 minutes.
[0086] A final preservative is prepared by mixing with a separately prepared aqueous solution of 2 to 4 weight%, preferably 3 weight%, of borate (borax:boric acid = 1:1 molar ratio).
[0087] After placing the wood into the immersion chamber and sealing it, a vacuum of -0.08 MPa is formed for 10 to 15 minutes to completely remove micro-holes and residual air inside the wood. While maintaining the vacuum, the prepared preservative is injected to ensure the wood is completely immersed. Subsequently, a pressure of 3 to 5 MPa, preferably 3.5 MPa, is applied for 12 to 15 minutes to forcibly inject the agent into the wood. This vacuum-pressure cycle is repeated 2 to 3 times for a total treatment of 30 to 45 minutes.
[0088] After the injection is complete, the excess agent is drained, the wood is removed, and aged at room temperature for 12 to 24 hours. During this process, the condensation reaction of the silane proceeds to form a Si-O-Si network, and simultaneously forms Si-OC bonds with the hydroxyl groups of the wood cell walls. If accelerated hardening is required, heat treatment can be performed at 40 to 60°C for 1 to 2 hours.
[0089] In the step (S50) of forming hydrogel microparticles, a hydrogel microparticle dispersion is prepared. An acrylate-based superabsorbent polymer (SAP) or a poly(acrylamide-co-acrylic acid) copolymer is classified to have an average particle size of 10 to 50 μm, preferably 20 to 40 μm. This is dispersed in deionized water at a concentration of 1 to 2 weight% and treated with an ultrasonic homogenizer for 5 minutes to prepare a uniform dispersion.
[0090] A hydrogel dispersion is applied to the wood surface using an airless spray or ultrasonic spray method. The application amount is controlled to 0.5 to 1.0 g / m², preferably 0.8 g / m². In particular, to selectively concentrate the application around the micro-hole entrance, an electrostatic spray technique or a masking template may be used. After application, the hydrogel particles are dried in a hot air dryer at 40 to 60°C for 10 to 20 minutes to ensure they are stably fixed to the hole entrance.
[0091] In the step of impregnating with wax (S60), paraffin wax (melting point 58-62°C) and carnauba wax (melting point 82-86°C) are mixed in a weight ratio of 7:3 to 9:1, preferably 8:2. The mixed wax is heated to 80 to 100°C, preferably 90°C, to completely melt it. After preheating the wood (60-70°C), it is immersed in the molten wax for 5 to 10 minutes, preferably 7 minutes.
[0092] When ultrasound (40 kHz) is applied during immersion, the penetration of the wax into the micro-holes is enhanced by more than 50%. After removing the wood, the excess wax on the surface is removed using a doctor blade or an air knife. The wood is left at room temperature for 30 to 60 minutes to allow the wax to solidify. During this process, the wax fills the inside of the micro-holes and the pores on the wood surface, forming a hydrophobic barrier.
[0093] In the step (S70) of coating and curing UV-PU, a UV-curable polyurethane resin is prepared. It is formulated with 60-70% acrylate-modified urethane oligomer, 20-30% reactive diluent (HDDA, TPGDA, etc.), 2-5% photoinitiator (Irgacure 184, 819, etc.), and 1-3% additives (leveling agent, defoamer, etc.). The viscosity is adjusted to 100 to 300 cPs.
[0094] If necessary, a primer may be applied first. The coating is applied at a rate of 30 to 60 g / m² using a roll coater, spray, or curtain coater. After each application, the coating is cured by irradiating with UV light of 385 to 405 nm wavelength at a rate of 1 to 2 J / cm². This process is repeated 2 to 3 times to achieve a total film thickness of 60 to 150 μm, preferably 120 μm. After the final coating, the film is post-cured at 25 to 35°C for 24 hours to maximize the crosslinking density.
[0095] When the entire process described above is completed, the manufacture of the preservative-treated wood according to the present invention is completed.
[0096] The technical concept of the present invention has been examined through the above examples.
[0097] It is obvious that a person skilled in the art to which the present invention pertains can make various modifications or changes to the embodiments described above from the description of the present invention. Furthermore, it is obvious that a person skilled in the art to which the present invention pertains can make various modifications including the technical concept according to the present invention from the description of the present invention, even if not explicitly illustrated or described, and such modifications still fall within the scope of the rights of the present invention. The embodiments described above with reference to the accompanying drawings are described for the purpose of explaining the present invention, and the scope of the rights of the present invention is not limited to these embodiments. Explanation of the symbols
[0098] 100: Preservative-treated wood 110: Microholes 111: Hall entrance 112: Lower part of the hole 113: Hall wall surface functionalization layer 120: Preservative retention layer 130: Hydrogel microparticles 140: Surface sealing layer 141: Wax impregnation layer 142: UV-curable polyurethane coating layer D1: Hall entrance diameter D2: Bottom diameter of the hole L: Hole depth
Claims
Claim 1 A preservative wood having laser-processed micro-holes, comprising: a plurality of micro-holes extending from the surface of a wood body into the interior by laser processing, with an entrance portion having a shape narrower than the bottom; a preservative holding layer injected through the micro-holes and retained inside the wood body; hydrogel micro-particles disposed at the entrance portion of the micro-holes to prevent the leaching of the preservative; and a surface sealing layer covering the surface of the wood body; wherein the micro-holes include a surface functionalization layer formed on the wall of the hole, and the surface functionalization layer is in a state where a carbonized layer is removed and polar groups are introduced by UV laser treatment, and the hydrogel micro-particles swell in response to moisture, and due to the hydrogel micro-particles, the micro-holes become smaller than the diameter of the entrance portion of the micro-holes in a dry state so as to open the micro-holes, and when swollen by moisture, the micro-holes become larger than the diameter of the entrance portion of the micro-holes so as to close the micro-holes so as to prevent the leaching of the preservative. Claim 2 Preservative wood having laser-processed microholes, characterized in that, in claim 1, the preservative-holding layer comprises a silane network structure that chemically bonds with a borate component and the surface functionalization layer. Claim 3 Preservative wood having laser-processed microholes, characterized in that, in claim 1, the surface sealing layer comprises a wax impregnation layer and a UV-curable polyurethane coating layer on top thereof.
Citation Information
Patent Citations
Full-intelligent production line for environment-friendly wood floors
CN113134887A
Composition for protecting lumber and decay durable lumber
JP2002137206A
Silicon-boric acid-based termite-proofing agent
JP2019034922A
Method for manufacturing preservative treated wood using a laser and preservative treated wood manufactured thereby
KR102690562B1